PEMANFAATAN PERPUSTAKAAN DESA SEBAGAI UPAYA INISIALISASI BUDAYA LITERASI MASYARAKAT DI DESA BALONGDOWO - Abdur Rohim; Muhamad Alim Cahyono; Muhamad Syaifudin (LPPM Universitas Islam Darul 'Ulum Lamongan, 2020)
Balongdowo Village is one of 25 villages located in Kepohbaru sub-district, Bojonegoro Regency, East Java Province. The village of Balongdowo has a village hall that has TV and WIFI facilities, and the problem here is that the password from the wifi can be used by the general public, resulting in children of student age coming to the village hall to play online games or just internet. And in terms of things that make children become lazy to learn, especially the culture of literacy that has recently been greatly reduced and the emergence of online games that make children forget the importance of learning, especially reading. For this reason, the writer has the thought to create a superior program from KKN in the village of Balongdowo, which is to create a village library. That aims to make children who are still students to read books more often and gradually leave the habit of playing online games. The aim of the library here is the development of human resources who are able to manage information and publications in line with the development of information technology, with the method of making a book twice a week, the results that can be achieved are making Balongdowo villagers love to read, and likewise the continuation of the program will be continued by village officials or village youth as well as a follow-up program for next year in order to be able to continue in the footsteps of village in balongdowo in 2019 which is to update the library which is very useful in the village.